Changes in water clarity in response to river discharges on the Great Barrier Reef continental shelf: 2002–2013. (5th May 2016) - Fabricius, K.E.; Logan, M.; Weeks, S.J.; Lewis, S.E.; Brodie, J.
Abstract: Water clarity is a key factor for the health of marine ecosystems. The Australian Great Barrier Reef (GBR) is located on a continental shelf, with >35 major seasonal rivers discharging into this 344, 000 km 2 tropical to subtropical ecosystem. This work investigates how river discharges affect water clarity in different zones along and across the GBR. For each day over 11 years (2002–2013) we calculated 'photic depth' as a proxy measure of water clarity (calibrated to be equivalent to Secchi depth), for each 1 km 2 pixel from MODIS-Aqua remote sensing data. Long-term and seasonal changes in photic depth were related to the daily discharge volumes of the nearest rivers, after statistically removing the effects of waves and tides on photic depth. The relationships between photic depths and rivers differed across and along the GBR. They typically declined from the coastal to offshore zones, and were strongest in proximity to rivers in agriculturally modified catchments. In most southern inner zones, photic depth declined consistently throughout the 11-year observation period; such long-term trend was not observed offshore nor in the northern regions. Averaged across the GBR, photic depths declined to 47% of local maximum values soon after the onset of river floods, and recovery to 95% of maximum values took on average 6 months (range: 150–260 days). The river effects were strongest at latitude 14.5°–19.0°S, where river loads are high and the continental shelf is narrow. Here, even offshore zones showed a >40% seasonal decline in photic depth, and 17–24% reductions in annual mean photic depth in years with large river nutrients and sediment loads. Our methodology is based on freely available data and tools and may be applied to other shelf systems, providing valuable insights in support of ecosystem management. Graphical abstract: Highlights: The 344, 000 km 2 Great Barrier Reef (GBR) is located on a shallow continental shelf. We show wide-spread, long-lasting losses in GBR water clarity after river floods. Across the GBR, rivers reduce water clarity by 50%, recovery takes ∼6 months. In some regions, rivers affect water clarity even on the outer shelf. Destructive starfish outbreaks originate in regions with greatest river effects.